PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT PADA PT. ASTRA HONDA MOTOR SEMARANG - Pratama, Salvandi Qito; Hermani, Agus; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2015)
Studying consumer behavior is an important thing that should be done by every company today. It is intended that the products they produce can be accepted by the public and can be successful in the competition between companies. This research was conducted at PT. Astra Honda Motor Semarang object Honda Beat. From the data known of buyers of Honda Beat Honda Beat fluctuations in the number of purchases and an increase in sales of Honda Beat branding but Honda Beat is still not able to shift the current Mio as the top brand. As a company engaged in the automotive, PT. Astra Honda Motor Semarang must build a good brand image since the beginning could through quality products so that the brand image in the minds of consumers and trustworthy and good quality products in order to increase the purchasing decisions of consumers by more varied, more qualified, and can understand what needed by the consumer.This study aimed to determine the effect of brand image (X1) and the quality of the product (X2) on purchase decisions (Y) Honda Beat. This type of research uses explanatory research with data collection method using interviews and data collection tools used questionnaires to a sample of 100 respondents buyer Honda Beat using purposive sampling method. Analysis technique using the validity, reliability, simple linear regression, multiple linear regression, t test and f by means of SPSS 17.Based on the results of statistical calculations in mind that the quality of products influence the purchasing decisions of 42.3%, while the brand image influence the purchasing decisions of 29.8%. Taken together brand image and product quality influence on purchasing decisions by 45.4%. While the remaining 54.6% is influenced by variables or other factors such as price, promotion, and others.Advice can be given to the company is to improve the brand image of Astra Honda Motor in order to be better that terkaitan the respondent trust company Honda. Besides the need for CSR (Corporate Social Responsibility) by PT. Astra Honda Motor as a concern for the environment and society. Companies must increase community activities Honda Beat users to further enhance the prestige of the user, so that it can assist management in making the latest innovations to the product of Honda Beat. If the product quality can be maintained Honda Beat is in itself a positive brand image of Honda Beat will also be formed.